BMI, POSTURAL CONTROL, PHYSICAL FUNCTION AND RISK OF WRIST FRACTURE IN MIDDLE AGED AND OLD ICELANDIC ADULTS. (11th November 2018) - Ramel, A; Baldursdottir, B; Geirsdottir, O; Whitney, S; Jonsson, P; Kristinsdottir, E
Abstract: Wrist fracture is the most common first fracture among Icelandic women, with a sharp rise in the incidence between 45–60 years of age and the third most common first fracture among men. Wrist fracture is known to be a strong predictor of hip fracture, which can result in decreased quality of life, death, and increased health cost. The aim of this study was to investigate whether BMI is related to postural control, vestibular function, mechanoreceptive sensation in the lower limbs, functional ability, perceived dizziness and with falls and wrist fractures in middle aged and old Icelandic adults. A case control study was conducted with 98 subjects aged 50–75 years having sustained a fall-related wrist fracture. Sex-, age- and physical activity-matched individuals (n=48), without previous history of wrist fractures, was control. Measurements included: Head-Shake test, Tuning fork, Biothesiometer, Semmes-Weinstein monofilaments, Sensory Organization Test, Five-times-sit-to-stand test, 10-meter-walk test, the Activities-specific Balance Confidence and the Dizziness Handicap Inventory scales. Linear and logistic regression models were used to find associations of BMI with a fall-related wrist fracture and related factors. Higher BMI was related to 1) higher risk of having experienced fractures earlier in life, 2) having more fall frequently; and 3) being in the fracture group. Although mechanoreceptive sensation is not related to BMI, higher BMI is related to poorer physical function and postural control as well as to poorer perceived confidence and increased dizziness. BMI is associated to an increased number of lifetime fractures, falls and wrist fractures.